Cytomegalovirus-specific T cells restricted for shared and donor human leukocyte antigens differentially impact on cytomegalovirus reactivation risk after allogeneic hematopoietic stem cell transplantation - Tassi, Elena; Noviello, Maddalena; De Simone, Pantaleo; Lupo-Stanghellini, Maria T.; Doglio, Matteo; Serio, Francesca; Abbati, Danilo; Beretta, Valeria; Valtolina, Veronica; Oliveira, Giacomo; Racca, Sara; Campodonico, Edoardo; et al. (Haematologica (Roma), 2023)
After allogeneic hematopoietic stem cell transplantation (HSCT), the emergence of circulating cytomegalovirus (CMV)- specific T cells correlates with protection from CMV reactivation, an important risk factor for non-relapse mortality. However, functional assays measuring CMV-specific cells are time-consuming and often inaccurate at early time-points. We report the results of a prospective single-center, non-interventional study that identified the enumeration of Dextramerpositive CMV-specific lymphocytes as a reliable and early predictor of viral reactivation. We longitudinally monitored 75 consecutive patients for 1 year after allogeneic HSCT (n=630 samples). The presence of ≥0.5 CMV-specific CD8+ cells/mL at day +45 was an independent protective factor from subsequent clinically relevant reactivation in univariate (P<0.01) and multivariate (P<0.05) analyses. Dextramer quantification correlated with functional assays measuring interferon-γ production, and allowed earlier identification of high-risk patients. In mismatched transplants, the comparative analysis of lymphocytes restricted by shared, donor- and host-specific HLA revealed the dominant role of thymic-independent CMV-specific reconstitution. Shared and donor-restricted CMV-specific T cells reconstituted with similar kinetics in recipients of CMV-seropositive donors, while donor-restricted T-cell reconstitution from CMV-seronegative grafts was impaired, indicating that in primary immunological responses the emergence of viral-specific T cells is largely sustained by antigen encounter on host infected cells rather than by cross-priming/presentation by non-infected donor-derived antigen-presenting cells. Multiparametric flow cytometry and high-dimensional analysis showed that shared-restricted CMV-specific lymphocytes display a more differentiated phenotype and increased persistence than donor-restricted counterparts. In this study, monitoring CMV-specific cells by Dextramer assay after allogeneic HSCT shed light on mechanisms of immune reconstitution and enabled risk stratification of patients, which could improve the clinical management of post-transplant CMV reactivations.